Hubungan Peer Attachment dengan Self Management Siswa dalam Belajar - Rahmi, Annisa Aulia; Firman, Firman (Lembaga Yasin AlSys, 2024)
This research is motivated by learning outcomes which are used as a benchmark to determine the level of student success. Ideally, students who get optimal learning outcomes have good self-management. However, students can still be found experiencing difficulties in self management, thus hampering the learning process and having an impact on learning outcomes. Student self-management can be influenced by external factors, one of which is the social environment, namely peers who have emotional ties or attachment (peer attachment). This research aims to determine the relationship between peer attachment and student self-management in studying at MAN 1 Padang City. This research uses quantitative methods with a correlational research type. The sample in this study was 155 students selected using the Simple Random Sampling technique. The data was processed using descriptive analysis techniques and Pearson product moment correlation analysis. The research results show that student peer attachment is in the high category with a percentage of (87.1%), student self-management is in the high category with a percentage of (77.4%) and there is a significant and positive relationship between peer attachment and self-management in students with The calculated r correlation value is 0.522 with a significance level of <0.00 at a moderate level of relationship.